Resolution of a Holliday junction by vaccinia topoisomerase requires a spacer DNA segment 3′ of the CCCTT↓ cleavage sites - Sekiguchi, JoAnn (Oxford University Press, 2000)
Vaccinia virus DNA topoisomerase catalyzes resolution of synthetic Holliday junctions in vitro. The mechanism entails concerted transesterifications at two recognition sites, 5′-CCCTT↓, that are opposed within a partially mobile four-way junction. Efficient resolution occurs on a junction with a 10 bp segment of branch mobility (5′-GCCCTTATCG) that extends 4 bp 3′ of the scissile phosphate. Here we report that resolution is decreased when branch mobility is limited to an 8 bp segment extending 2 bp 3′ of the cleavage site and then eliminated when branch mobility is confined to the 6 bp GCCCTT sequence 5′ of the scissile phosphate. We surmise that a spacer region 3′ of CCCTT is needed for simultaneous cleavage at two opposing sites at the junction. Branch mobility is not required for reaction chemistry at a junction, because topoisomerase cleaves a single CCCTT site in a non-mobile four-way junction where the scissile phosphate is at the crossover point. The junction resolvase activity of topoisomerase may be involved in forming the hairpin telomeres of the vaccinia genome.